ANALISIS PENGUKURAN PERSEDIAAN DAN PENYAJIANNYA DALAM LAPORAN KEUANGAN - Elfreda Aplonia Lau (Prodi Ilmu Administrasi Negara, 2019)
Inventory in accounting shows the value of an item produced for saleor consumed and the value of an item purchased for sale. There are manymethods used to make inventory measurements or assessments. However, thisstudy focuses on a review of how to measure inventory values based on the FirstEntry First (MPKP) or First In First Out (FIFO) method, the Last Enter FirstOut (MTKP) or Last In First Out (LIFO) method, the Average Method ,Identification Method and review whether the use of the method producesdifferent final inventory quantities. In this study also discussed the effects onincome that can be followed by presentation in financial statements. Thefinancial statements intended in this study are limited to income reports or NetProfitThe results showed that the measurement of inventory cost based onthe cost flow method using the FIFO, LIFO method, Simple Average, WeightedAverage and Special Cost Method displays the different final inventory values,as well as the measurement method. impact on the presentation of incomestatements.FIFO produces the smallest HPP so that the highest net income andtax. LIFO produces the largest HPP so that it produces low net income andtaxes. The simple and weighted average method produces a difference in coststhat are not so significant, but both differ in the way they are calculated. Thespecial identification method ranks second in profit. This finding shows thatcompanies (managers) need to know the selection of inventory valuationmethods used and their effect on earnings.